The “Pricebo Effect”: How Prices Could Influence Cannabis Quality Perception and its Implications on Price Policies - Carrasco Villanueva, Marco Alberto (2018)
The term “pricebo effect” is coined in the present study to refer to the way that prices could shape consumers’ quality perception of a good. This effect may start from prices modifying expectations, to shaping the perceived quality of the product, and finally affecting the consumer’s demands. This study has analyzed the existence of the pricebo effect for the case of cannabis—a product that gives some interesting advantages over goods analyzed in previous studies. Although there was not a significant effect identified for herbal cannabis (commonly known as weed or marijuana) the analyses identified a stable and significant pricebo effect for resin cannabis— commonly known as hash or hashish. Results are discussed considering the differences in sample size for each type, as well as the existing literature about placebos and the role of prices on perception. As the results support the plausibility of a pricebo effect in certain contexts, price policy implications are discussed as well— as consumers may be susceptible to being tricked by firms, to a certain degree. JEL: D03, E21, E64, L65, L15.